2021
DOI: 10.3390/jcm10132791
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Associates with Rheumatoid Arthritis Risk in Overweight and Obesity Independently of Other Adipokines

Abstract: We recently reported that increased serum adiponectin was associated with rheumatoid arthritis (RA) risk in subjects with obesity. We hereby aim to determine if other adipokines associate with RA risk and if the association between adiponectin and RA is independent of other adipokines. Two nested-case control studies were performed in two different cohorts: 82 participants of the Swedish Obese Subjects (SOS) study who developed RA during follow-up matched with 410 controls, and 88 matched pairs from the Medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Obesity is one of the major conditions that gives rise to a myriad of comorbid, inflammation driven, chronic diseases particularly as aging progresses [ 62 , 63 ]. Table 2 illustrates examples of 43 comorbid NCDs for obesity [ 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 ]. The obese population carries one of the highest risks for multiple future NCDs of any disease-burdened cohort.…”
Section: Two High-impact Examples Of Ncdsmentioning
confidence: 99%
“…Obesity is one of the major conditions that gives rise to a myriad of comorbid, inflammation driven, chronic diseases particularly as aging progresses [ 62 , 63 ]. Table 2 illustrates examples of 43 comorbid NCDs for obesity [ 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 ]. The obese population carries one of the highest risks for multiple future NCDs of any disease-burdened cohort.…”
Section: Two High-impact Examples Of Ncdsmentioning
confidence: 99%
“…The complex and multiple roles of adiponectin include immune regulation and alteration of the microenvironment through regulation of angiogenesis. Some studies reported increased plasma levels of adiponectin in RA patients, which correlated positively with the parameters of disease activity, clinical symptoms, and progression of joint erosions and also correlated with the expression of other mediators involved in inflammation, severity of joint destruction, and response to treatment [ 15 , 21 , 22 , 23 , 24 ]. Other studies have not found elevated plasma adiponectin concentrations in RA patients [ 25 , 26 ], or even a negative correlation between adiponectin concentrations and disease activity parameters [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“… 8 It has been reported that leptin may stimulate fibroblast-like cells in RA to produce proinflammatory cytokines. 5 In most studies in literature, leptin levels were reported to be increased in patients with RA; some studies found no significant difference or reduced leptin levels when compared to healthy controls or patients with osteoarthritis. 6 , 8 The positive correlation was found between leptin levels and disease activity score (DAS28) or with C-reactive protein (CRP) concentration.…”
Section: Introductionmentioning
confidence: 94%
“…It has been reported that obesity is the risk factor for RA, and not only for metabolic disorders such as metabolic syndrome or type 2 diabetes. 4,5 On the contrary, high-grade inflammatory activity in the course of RA may be associated with loss of body cell mass and consequently body mass reduction, defined as rheumatoid cachexia. 6 Adipose tissue seems to be the largest endocrine organ that produces high amounts of several biologically active molecules, called adipokines.…”
Section: Introductionmentioning
confidence: 99%